2018
DOI: 10.1111/nyas.13922
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine diphosphate regulates MMP2 and MMP9 activity in malignant mesothelioma cells

Abstract: Although an association between cancer progression and matrix metalloproteinase (MMP) 2 and MPP9 expression has been known, the expression, nuclear localization, and physiologically controlled activation of these two MMPs have not been investigated in malignant mesothelioma cells. We examined the expression and intracellular localization of MMP2/9 in ZL55 malignant mesothelioma cells, as well as their regulation by ADP. Using real-time PCR, we showed that activation of the P2Y1 receptor by ADP increased the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…VEGF-A is involved in CCL3-dependent angiogenesis in osteosarcoma [ 23 ] and is also upregulated downstream of the CCL3–CCR5 axis in oral squamous cell carcinoma [ 27 ]. Activating the PI3K/Akt and MEK/ERK pathways induces the expressions of MMP-2, MMP-9, and VEGF-A in various malignancies including ESCC [ 62 65 ]. Our present results demonstrated that treatment with rhCCL3 upregulated the MMP2 mRNA expression in three ESCC cell lines universally, and the VEGFA mRNA expression in two ESCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A is involved in CCL3-dependent angiogenesis in osteosarcoma [ 23 ] and is also upregulated downstream of the CCL3–CCR5 axis in oral squamous cell carcinoma [ 27 ]. Activating the PI3K/Akt and MEK/ERK pathways induces the expressions of MMP-2, MMP-9, and VEGF-A in various malignancies including ESCC [ 62 65 ]. Our present results demonstrated that treatment with rhCCL3 upregulated the MMP2 mRNA expression in three ESCC cell lines universally, and the VEGFA mRNA expression in two ESCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Troponin subunits enhance the growth and migration of neoplastic cells (13). Adenosine diphosphate generated by CK produces energy for cellular functions, and stimulates the degradation of the extracellular matrix (14). We speculate that the accumulation of cardiac-specific proteins/enzymes may contribute to disease progression in a tumor environment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also implicated SFKs in regulating the expression of MMPs in MM [45], in which these ECM-degrading enzymes associate with more invasive and aggressive behavior [99][100][101]. In particular, this study showed that activation of the G protein-coupled purinergic receptor P2Y1 by Receptor tyrosine kinases (RTKs) are frequently overexpressed and hyperactivated in MM and cooperatively interact with SRC to signal to downstream effectors, such as the mitogen-activated protein kinase (MAPK) and AKT pathways, which promote cell proliferation and survival.…”
Section: Role Of Sfks In Molecular Pathways Regulating Cell Adhesionmentioning
confidence: 98%
“…A recent study also implicated SFKs in regulating the expression of MMPs in MM [45], in which these ECM-degrading enzymes associate with more invasive and aggressive behavior [99][100][101]. In particular, this study showed that activation of the G protein-coupled purinergic receptor P2Y1 by adenosine diphosphate (ADP) triggered SFK-mediated upregulation of MMP2/9 in MM cells [45]. Interestingly, this work also revealed a possible non-canonical nuclear role of MMP2/9 in the ZL55 human epithelioid MM cell line; such nuclear function of MMPs was previously identified in other tumors [102] but remains to be further addressed in MM.…”
Section: Role Of Sfks In Molecular Pathways Regulating Cell Adhesionmentioning
confidence: 98%
See 1 more Smart Citation